Paper Skin Multisensory Platform for Simultaneous Environmental Monitoring. Issue 1 (19th February 2016) - Nassar, Joanna M.; Cordero, Marlon D.; Kutbee, Arwa T.; Karimi, Muhammad A.; Sevilla, Galo A. Torres; Hussain, Aftab M.; Shamim, Atif; Hussain, Muhammad M.
Abstract : Human skin and hair can simultaneously feel pressure, temperature, humidity, strain, and flow—great inspirations for applications such as artificial skins for burn and acid victims, robotics, and vehicular technology. Previous efforts in this direction use sophisticated materials or processes. Chemically functionalized, inkjet printed or vacuum‐technology‐processed papers albeit cheap have shown limited functionalities. Thus, performance and/or functionalities per cost have been limited. Here, a scalable "garage" fabrication approach is shown using off‐the‐shelf inexpensive household elements such as aluminum foil, scotch tapes, sticky‐notes, napkins, and sponges to build "paper skin" with simultaneous real‐time sensing capability of pressure, temperature, humidity, proximity, pH, and flow. Enabling the basic principles of porosity, adsorption, and dimensions of these materials, a fully functioning distributed sensor network platform is reported, which, for the first time, can sense the vitals of its carrier (body temperature, blood pressure, heart rate, and skin hydration) and the surrounding environment. Abstract : A flexible, paper‐based artificial skin that integrates the maximum number of sensory functionalities found in human skin is developed. The fabricated 3D stacked platform uses nonfunctionalized off‐the‐shelf materials to demonstrate high performance, low‐cost, flexible, and multifunctional sensors network, capable of simultaneous and real‐time monitoring of environmental external stimuli such as pressure, touch, temperature, humidity, proximity, pH, and flow.